Ammi Analysis Of Wheat Genotypes Under Restricted Irrigated Timely Sown Conditions For Peninsular Zone Of India (Applied Biological Research, 2020)
Variable yield performances of cereal crops have been reported across the  environments while prior to the release of cultivars in wheat genotype x  environment (G x E) effects are estimated. Crossover G x E interaction  decreases the efficiency of cultivar selection by reducing the correlation  between phenotype- and genotype-values. In present study a number of  AMMI based measures were compared for the wheat genotypes evaluated  under Peninsular zone of India. Genotypes ‘MPO 1336’, ‘HI 8805’ and ‘NIAW 3170’ identified by the values of EV1, D1, ASTAB1 and SIPC1  favored ‘MACS 4058’, ‘DBW 93’ and ‘GW 1346’. Measures based on two  IPS’s (ASV & ASV1) recommended ‘MACS 4059’, ‘UAS 446’ and ‘NIAW  3170’ genotypes. Analytic measures MASV and MASV1 selected ‘MACS  4059’, ‘UAS 446’ and ‘MACS 6696’ wheat genotypes for stable  performance. HM, PRVG and MHPRVG identified ‘UAS 446’, ‘MACS  6695’ and ‘HI 1605’ consistent yield. Biplot analysis showed larger cluster  of D2, EV2, ASV, ASV1 and ASTAB2. ASV expressed choice for ‘HI1605’,  MACS 6695’and ‘HI 8805’ while ASV1 recommended ‘MACS 6695’,  ‘HI1605’ and ‘HI 8805’ genotypes for the 2nd year (2018-19). MASV  measure found ‘HI1605’, ‘NIDW 1149’, HI 8802 of choice and MASV1  settled for ‘HI1 605’, ‘HI 8805’ and ‘NIDW 1149’ genotypes. Wheat  genotypes ‘NIAW 3170’, ‘MACS 6695’ and ‘MACS 6696’ were identified  by HM, PRVG and MHPRVG measures. Larger cluster consisted of EV1,  D1, D2, EV2, ASV, ASV1, MASV, MASV1, ASTAB1 and ASTAB2 in  biplot analysis. Mean, HM, PRVG, MHPRVG and GAI along with SIPC2  and SIPC3 clubbed in 4th cluster. Analytic measures of adaptability  exhibited affiliation with measure-based values of IPC scores.
Keywords: AMMI model; ASV; ASTAB; biplot analysis; MASV; SIPC